Infrastructure Bottlenecks as Opportunity for Local Development: The Case of Decentralized Green-Hydrogen Projects - Benedikt Walker; Britta Klagge (Tijdschrift voor economische en sociale geografie, 2024)
Energy geography has not scrutinized the role of energy infrastructures and market design for decentralized energy production and local development. The paper addresses this research gap by looking at the emerging green-hydrogen market in Germany. We argue, first, that the capacity and geography of infrastructures and associated bottlenecks determine how supply and demand can be matched at different scales. Second, market design and associated controversies over infrastructure bottlenecks are important for understanding the green-hydrogen market and its geography and financing. Conceptually, we draw on the geography-of-markets literature. Empirically, we show how infrastructure bottlenecks and market design link the green-hydrogen to the renewable-electricity market. As long as the market design requires green-hydrogen production in geographical and temporal correlation with renewable-electricity generation, the geography of green-hydrogen production follows the geography of renewable-electricity generation. Moreover, bottlenecks in transportation infrastructures offer a window of opportunity for decentralized production and local development.
Keywords: 330; energy geography; energy market; hydrogen; transportation infrastructure; market design; Germany